P6 Fatty acids impair HIF1α activation and suppress metabolic adaptation to hypoxia in insulin resistance. (26th October 2016) - Dodd, MS; Luiken, JJFP; Glatz, JFC; Tyler, DJ; Heather, LC
Abstract : The type 2 diabetic heart is metabolically abnormal, with increased fatty acid utilisation and decreased survival post-myocardial infarction (MI). Following an MI, hypoxia-inducible factor-1α (HIF1α) promotes anaerobic glycolysis and suppresses aerobic metabolism. We questioned whether diabetes modified HIF signalling and the response to hypoxia. HL-1 cardiomyocytes were incubated in palmitate (500 µM) and insulin (50 nM) for 8 h, to induce insulin resistance. When exposed to hypoxia (2% O2 for 16 h), control cells elevated HIF1α protein levels 15-fold, increased downstream targets prolyl hydroxylase domain (PHD) 2 and 3 by 320 and 475%, GLUT1 by 265% and VEGF by 410%. This increased glucose utilisation and lactate efflux in hypoxic control cells. In contrast, HIF1α activation in insulin resistant cells was absent following exposure to hypoxia, with no induction of downstream targets or flux through anaerobic pathways. This was specific to HIF signalling pathways, as hypoxic activation of ATF1 and its downstream target UCP3 was not impaired by insulin resistance. Palmitate and oleate alone were able to suppress hypoxia-induced HIF1α activation in a concentration-dependent manner. HIF1α protein levels and downstream targets could be partially restored in insulin resistant cells by treatment with the PHD inhibitor; DMOG. DMOG (1 mM) increased lactate efflux, HIF1α protein and HIF1β, and partially restored GLUT1 protein levels. In conclusion, insulin resistance impairs hypoxia-induced HIF1α activation and downstream metabolic adaptation to hypoxia. Here we demonstrate that this is mediated by a fatty acid-induced inhibition of HIF1α activation, providing a novel mechanism for how myocardial lipids impair recovery post-MI.